2017
DOI: 10.1242/dev.141952
|View full text |Cite
|
Sign up to set email alerts
|

Distinct intracellular Ca2+ dynamics regulate apical constriction and differentially contribute to neural tube closure

Abstract: Early in the development of the central nervous system, progenitor cells undergo a shape change, called apical constriction, that triggers the neural plate to form a tubular structure. How apical constriction in the neural plate is controlled and how it contributes to tissue morphogenesis are not fully understood. In this study, we show that intracellular calcium ions (Ca 2+ ) are required for Xenopus neural tube formation and that there are two types of Ca 2+ -concentration changes, a single-cell and a multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 45 publications
6
73
1
Order By: Relevance
“…The detailed mechanism of how Ca 2+ is functionally linked to contractile actomyosin also remains unclear, although there is no doubt that Ca 2+ is involved in regulation of contractility in many cell types [10][11][12][13][14]16]. It is clear that Ca 2+ does not directly act on actomyosin similar to the contractile system involving troponin C, given the time lag between Ca 2+ burst and contractility in the range of many seconds.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanism of how Ca 2+ is functionally linked to contractile actomyosin also remains unclear, although there is no doubt that Ca 2+ is involved in regulation of contractility in many cell types [10][11][12][13][14]16]. It is clear that Ca 2+ does not directly act on actomyosin similar to the contractile system involving troponin C, given the time lag between Ca 2+ burst and contractility in the range of many seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies reveal that intracellular calcium levels are crucial for neural tube closure, a direct link between calcium and apical constriction during neurulation has only recently been uncovered by two recent studies using live imaging of frog embryos. These studies revealed that apical constriction during neurulation involves cellautonomous and asynchronous pulsed apical contractions that are preceded by flashes of calcium (Christodoulou and Skourides, 2015;Suzuki et al, 2017). These calcium pulses also correlate with accumulation of F-actin in the medial region of neuroepithelial cells, suggesting that calcium regulates apical constriction by influencing actin dynamics and/or myosin contractility.…”
Section: Introductionmentioning
confidence: 91%
“…Assembly of this actomyosin network occurs via oscillatory constrictions with gradually decreasing amplitude, akin to the ratchet model initially proposed in invertebrates [50][51][52] and later reported during neural tube closure in Xenopus 53 . We further show that disruption of myosin impairs NF convergence, possibly by contributing a "pulling force" on the NFs or by clearing the dorsal midline of eye field cells.…”
Section: Discussionmentioning
confidence: 77%